2017
DOI: 10.1021/acs.jafc.6b04948
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of S-Allylcysteine-Enriched Black Garlic Juice and Its Antidiabetic Effects in Streptozotocin-Induced Insulin-Deficient Mice

Abstract: S-Allylcysteine (SAC), produced in large amounts during the aging process of garlic via enzymatic hydrolysis, is known as a key compound responsible for the multiple pharmacological activities of aged black garlic. This study investigated the effects of enzyme- and high hydrostatic pressure (HHP)-assisted extraction on the content of the bioactive compounds, including SAC, in black garlic juice (BGJ) and evaluated the antidiabetic effects of SAC-enriched BGJ in streptozotocin (STZ)-treated mice. The aging proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
4
15
0
1
Order By: Relevance
“…ABG reduces insulin resistance and serum total cholesterol and triglyceride levels, and increases the high density lipoprotein (HDL) cholesterol levels in db/db mice through antioxidant activity [ 21 ]. The SAC enriched black garlic juice gives anti-diabetic effects in streptozotocin-induced insulin deficient mice [ 65 ]. ABG reduces thiobarbituric acid reactive substances (TBARS) in serum, liver, and kidneys through increasing activities of antioxidant enzyme in streptozotocin-induced diabetic rats [ 66 ].…”
Section: Properties Of Abgmentioning
confidence: 99%
“…ABG reduces insulin resistance and serum total cholesterol and triglyceride levels, and increases the high density lipoprotein (HDL) cholesterol levels in db/db mice through antioxidant activity [ 21 ]. The SAC enriched black garlic juice gives anti-diabetic effects in streptozotocin-induced insulin deficient mice [ 65 ]. ABG reduces thiobarbituric acid reactive substances (TBARS) in serum, liver, and kidneys through increasing activities of antioxidant enzyme in streptozotocin-induced diabetic rats [ 66 ].…”
Section: Properties Of Abgmentioning
confidence: 99%
“…A recent study showed that SAC could suppress hepatocyte growth factor-induced migration and invasion in nasopharyngeal cancer cells ( Cho et al, 2015 ). SAC could also exert anti-diabetic effects by means of improving beta-cell function and reducing glycemia ( Kim et al, 2017 ).…”
Section: Donors Of Hydrogen Sulfidementioning
confidence: 99%
“…Aged black garlic also has been largely attributed to as having cardioprotective, antidiabetic, hepatoprotective, antimicrobial, antioxidant, anti-inflammatory, antithrombotic, antihypertensive, and antihyperlipidemic properties. (Shaarawy et al, 2009;Obioha, Suru, OlaMudathir, & Faremi, 2009;García-Villalón et al, 2016;Kim et al, 2017;Kimura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%